Why don't you get a horse, Sam Adams? - Fritz, Jean.; Hyman, Trina Schart (New York : Scholastic, 1974)
A brief biography of Samuel Adams describing his activities in stirring up the revolt against the British and how he was finally persuaded to learn to ride a horse.
Keywords: Adams, Samuel, -- 1722-1803 -- Juvenile literature; Adams, Samuel, -- 1722-1803.; United States -- History -- Revolution, 1775-1783.